Cultural Change and Human Behavior: Evolution or Development? - Fave, Antonella Delle; Massimini, Fausto (Crossing the Border: International Journal of Interdisciplinary Studies, 2015)
The study of cultures in today’s world has become a major academic exercise. There are many challenges and problems for human beings that are created by the relationship between cultural inheritance and individuals, namely, through modernization and globalization processes. ! e immediate outcomes of these challenges and problems are ethnic conflicts, cultural clash and other cultural competitions. In order to maintain peace in the world and foster the mutual cooperation among the individuals, each individual has to be an active participant in the attainment of a sustainable development of the whole human system. The main focus of this paper, thus, is to analyze human behavior, as a way of understanding underlying powers of the interplay of biology and culture. Crossing the Border: International Journal of Interdisciplinary Studies Vol.3(1) 2015: 41-52